What the socioeconomic MHDI and CPI indicators reveal in different urban realities: São Paulo and Fortaleza, Brazil (Terr@ Plural, 2020)
This paper aims to analyze the possibilities and limitations of using synthetic indicators using two globally applied systems as a reference, the Municipal Human Development Index (MHDI) and the City Prosperity Index-CPI. Therefore, aims to analyze two different urban realities: São Paulo (SP) and Fortaleza (CE), based on two indexes: The Municipal Human Development Index (MHDI) of the United Nations Program (PNUD) and the City Prosperity Index (CPI) started in 2012 by the United Nations Program for Human Settlements (ONU-Habitat). The MHDI is based on indicators in three dimensions: longevity, education, and family income, while the CPI measures the characteristics of the municipalities in terms of productivity, infrastructure, inclusion and social equity, quality of life, environmental sustainability, and governance and legislation. Comparative analysis of the results of indicators that reveal the limitations and potentials considered for the construction of improved systems indicators. It is noticed, from the analyzed properties, factors that go beyond the character of the indicator must be considered. Efficiency in the collection, acceptance of the target audience, and qualitative analysis must be considered in use for the adequate measurement of the actions developed in the municipal public management and for the understanding of the appropriate and social changes in the cities.
Keywords: Urban planning; Urbanization; Public Management